2016
DOI: 10.1177/1475725716680460
|View full text |Cite
|
Sign up to set email alerts
|

The Big Five, Learning Goals, Exam Preparedness, and Preference for Flipped Classroom Teaching: Evidence from a Large Psychology Undergraduate Cohort

Abstract: Previous research has found that the flipped classroom (i.e., learning prior to the lecture, and using the lecture time for consolidating knowledge) increases students' deep learning, and has an association with improved grades. However, not all students benefit equally from flipping the classroom, and there may be important individual differences that influence preference for different teaching styles. In the present study, undergraduate Psychology students (n ¼ 200) answered questions about exam preparedness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…However, within FC approach, the question of how personality traits may affect students’ interaction with a learning environment, their preferences, willing to collaborative work and learning experiences is examined. Lyons, Limniou, Schermbrucker, Hands, and Downes ( 2017 ) researched how personality affects students’ preferences, decision-making processes, intention to learn and readiness to education at FC compared to traditional courses. The related study identified the Big Five Personality Traits (in word Openness, Conscientiousness, Agreeableness, Extraversion and Neuroticism) as individual differences affecting the preference of different learning and teaching approaches.…”
Section: Conceptual Background and Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…However, within FC approach, the question of how personality traits may affect students’ interaction with a learning environment, their preferences, willing to collaborative work and learning experiences is examined. Lyons, Limniou, Schermbrucker, Hands, and Downes ( 2017 ) researched how personality affects students’ preferences, decision-making processes, intention to learn and readiness to education at FC compared to traditional courses. The related study identified the Big Five Personality Traits (in word Openness, Conscientiousness, Agreeableness, Extraversion and Neuroticism) as individual differences affecting the preference of different learning and teaching approaches.…”
Section: Conceptual Background and Literature Reviewmentioning
confidence: 99%
“…The related study identified the Big Five Personality Traits (in word Openness, Conscientiousness, Agreeableness, Extraversion and Neuroticism) as individual differences affecting the preference of different learning and teaching approaches. Lyons et al ( 2017 ) emphasized that interaction preference at FC has a relation with high Agreeableness and low Neuroticism, and meaningful learning will be achieved as these personality traits encourage participation in collaborative works. Furthermore, the reflective learning stills which include transfer of learned information to problem statuses are in relation to Conscientiousness and Openness to experience (Komarraju et al, 2011 ; Meyer et al, 2019 ).…”
Section: Conceptual Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…El Flipped Classroom contribuye a promover competencias afines al emprendimiento, por cuanto el estudiante requiere trazar un plan de trabajo para lograr las metas establecidas en la planificación curricular; además es, a partir de orientaciones o asesoramientos por parte del docente, quien desarrolla una serie de actividades demostrativas del aprendizaje alcanzado, el cual se caracteriza por ser duradero en el tiempo (Mero-Chávez, et al, 2019 En este contexto, el cooperativo y colaborativo se potencia en la medida que el flipped classroom, se asocia con rasgos de la personalidad como la amabilidad, afabilidad, caracterizadas por el disfrute del estudiante al participar en la clase (Lyons, et al, 2017), planteándose además que los estudiantes con rasgos de personalidad conflictiva, presentan inconvenientes para integrarse activamente en los subprocesos desarrollados a través del flipped classroom o aula invertida.…”
Section: Introductionunclassified